Mechanisms of negative differential resistance in glutamine-functionalized WS2 quantum dots. (24th November 2021) - Feria, Denice N; Sharma, Sonia; Chen, Yu-Ting; Weng, Zhi-Ying; Chiu, Kuo-Pin; Hsu, Jy-Shan; Hsu, Ching-Ling; Yuan, Chi-Tsu; Lin, Tai-Yuan; Shen, Ji-Lin
Abstract: Understanding the mechanism of the negative differential resistance (NDR) in transition metal dichalcogenides is essential for fundamental science and the development of electronic devices. Here, the NDR of the current–voltage characteristics was observed based on the glutamine-functionalized WS2 quantum dots (QDs). The NDR effect can be adjusted by varying the applied voltage range, air pressure, surrounding gases, and relative humidity. A peak-to-valley current ratio as high as 6.3 has been achieved at room temperature. Carrier trapping induced by water molecules was suggested to be responsible for the mechanism of the NDR in the glutamine-functionalized WS2 QDs. Investigating the NDR of WS2 QDs may promote the development of memory applications and emerging devices.